Self-crystallization of uniformly oriented zeolitic imidazolate framework films at air–water interfaces. Issue 30 (12th July 2019) - Su, Jingyi; Wu, Wufeng; Li, Zhanjun; Li, Wanbin
Abstract : ZIF-8 films with highly out-of-plane orientation and smooth–rough Janus crystalline facets are crystallized at air–water interfaces under mild conditions. Abstract : Gas–liquid interfaces with unique physicochemical properties have great potential for the self-assembly of many materials. Herein, a concept of the autonomous self-crystallization of MOF films at air–water interfaces is reported. The free-standing ZIF-8 films with a large area of about 20 cm 2 can be preferentially assembled only at the water surface. Under the influence of the atomically well-defined and amphiphilic interface on anisotropically polar linkers, the thus-prepared ZIF-8 films exhibit highly out-of-plane orientation and smooth–rough Janus crystalline facets.